2007
DOI: 10.1088/1741-2560/4/4/001
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous neural interactions assessed by magnetoencephalography: a functional biomarker for brain disorders

Abstract: We report on a test to assess the dynamic brain function at high temporal resolution using magnetoencephalography (MEG) for 45-60 s. After fitting an autoregressive integrative moving average (ARIMA) model and taking the stationary residuals, all pairwise, zero-lag, partial cross-correlations P CC 0 ij and their z-transforms z 0 ij between i and j sensors were calculated, providing estimates of the strength and sign (positive, negative) of direct synchronous coupling at 1 ms temporal resolution. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 18 publications
5
106
0
Order By: Relevance
“…We then used a stepwise linear discriminant analysis (17) to test how well patterns of MEG signals could classify periods of motion perception. To do this, we used the mean MEG signals from the epochs described above.…”
Section: Methodsmentioning
confidence: 99%
“…We then used a stepwise linear discriminant analysis (17) to test how well patterns of MEG signals could classify periods of motion perception. To do this, we used the mean MEG signals from the epochs described above.…”
Section: Methodsmentioning
confidence: 99%
“…The results prove that our method is comparable with other methods in this area. In order to prove the effectiveness and compatibility of the proposed method, we have compared the proposed method with several state-of-the-art methods including, Ford et al [26], Pokrajac et al [27], and Georgopoulos et al [28] methods, and the results are shown in table 3. …”
Section: Case Number Diagnosismentioning
confidence: 99%
“…However, given the prevalence of ASD, the potential benefits of using MEG as a screening tool to allow early identification of the illness make the technique a valuable one. Georgopoulos et al (2007) made MEG recordings from 142 individuals whilst they fixated on a spot of light for 45-60 seconds. The analysis stream utilised the sensor information and assessed zero-lag cross-correlations in order to provide an estimate of synchronous coupling.…”
Section: Future Applicationsmentioning
confidence: 99%